FTO deficiency in older livers exacerbates ferroptosis during ischaemia/reperfusion injury by upregulating ACSL4 and TFRC - Li, Rong; Yan, Xijing; Xiao, Cuicui; Wang, Tingting; Li, Xuejiao; Hu, Zhongying; Liang, Jinliang; Zhang, Jiebin; Cai, Jianye; Sui, Xin; Liu, Qiuli; Wu, Manli; et al. (Nature communications, 2024)
Older livers are more prone to hepatic ischaemia/reperfusion injury (HIRI), which severely limits their utilization in liver transplantation. The potential mechanism remains unclear. Here, we demonstrate older livers exhibit increased ferroptosis during HIRI. Inhibiting ferroptosis significantly attenuates older HIRI phenotypes. Mass spectrometry reveals that fat mass and obesity-associated gene (FTO) expression is downregulated in older livers, especially during HIRI. Overexpressing FTO improves older HIRI phenotypes by inhibiting ferroptosis. Mechanistically, acyl-CoA synthetase long chain family 4 (ACSL4) and transferrin receptor protein 1 (TFRC), two key positive contributors to ferroptosis, are FTO targets. For ameliorative effect, FTO requires the inhibition of Acsl4 and Tfrc mRNA stability in a m6A-dependent manner. Furthermore, we demonstrate nicotinamide mononucleotide can upregulate FTO demethylase activity, suppressing ferroptosis and decreasing older HIRI. Collectively, these findings reveal an FTO-ACSL4/TFRC regulatory pathway that contributes to the pathogenesis of older HIRI, providing insight into the clinical translation of strategies related to the demethylase activity of FTO to improve graft function after older donor liver transplantation. Transplanted older livers are prone to injury through unclear mechanisms, precluding effective treatment development. Here, the authors show that decreased FTO expression in older livers inhibits Acsl4 and Tfrc mRNA stability in an m6A-dependent manner, increasing cell death in older donor livers.